Development and disease-specific regulation of RNA splicing in cardiovascular system - Jiang, Jinxiu; Wu, Hongchun; Ji, Yabo; Han, Kunjun; Tang, Jun-Ming; Hu, Shijun; Lei, Wei (Frontiers in Cell and Developmental Biology, 2024)
Alternative splicing is a complex gene regulatory process that distinguishes itself from canonical splicing by rearranging the introns and exons of an immature pre-mRNA transcript. This process plays a vital role in enhancing transcriptomic and proteomic diversity from the genome. Alternative splicing has emerged as a pivotal mechanism governing complex biological processes during both heart development and the development of cardiovascular diseases. Multiple alternative splicing factors are involved in a synergistic or antagonistic manner in the regulation of important genes in relevant physiological processes. Notably, circular RNAs have only recently garnered attention for their tissue-specific expression patterns and regulatory functions. This resurgence of interest has prompted a reevaluation of the topic. Here, we provide an overview of our current understanding of alternative splicing mechanisms and the regulatory roles of alternative splicing factors in cardiovascular development and pathological process of different cardiovascular diseases, including cardiomyopathy, myocardial infarction, heart failure and atherosclerosis.